Inclusion of Family Therapy in Rehabilitation Program of Substance Abuse and Its Efficacious Implementation - EKŞİ, HALİL (SAGE PUBLICATIONS INC, 2019)
The family has been described as the center or heart of societal relationships. There has been a historic neglect of research in area of counseling for the family members of substance abusers. As result, treatment for individual family members affected by alcoholism and drug addiction remains a neglected component of majority of addiction programs. The study used a sample of 36 families who participated in family therapy intensive outpatient and inpatient treatment program during 2 years. This study explored the efficacy of family-based treatment in changing family's attitudes toward people with addiction and toward specific relative with addiction. The participants were in two groups; ethnographic technique of action research model was used. Participants in the treatment group received treatment session and participants in the control group did not receive treatment session but had a general treatment program in health centers. This study had two phases: (1) recruiting, selecting, interviewing, and determining eligibility of family members from both groups in the study and (2) applying the intervention to the treatment group with the help of cognitive-behavioral group counseling. This treatment program comprised of solution-focused family skilled training therapy, action learning techniques, community and peer mentorship, and parent training was effective in reducing addicts drug ingestion, changing their attitudes about drug use, increasing knowledge of the physical consequences of drug use, and improving competent behaviors. Family therapy enhanced family resilience, structure, and strong ties; the program improved problem-solving skills, coping skills, and family resiliency levels of the addicts.
Keywords: substance addiction; family life skills; action research; cognitive-behavioral counseling; family therapy; ADDICTION; PREVENTION; STYLES